Chapter 13 Safe European home Where did you go? On immigration, the b/ ordered self, and the territorial home - Laine, Jussi; Moyo, Inocent; Nshimbi, Christopher Changwe (Taylor & Francis, 2020)
This book challenges the common European notions about African migration to Europe and offers a holistic understanding of the current situation in Africa. It advocates a need to rethink Africa-Europe relations and view migration and borders as a resource rather than sources of a crisis.